2021
DOI: 10.3390/antiox10040508
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quantitative Proteomic Analysis of Nitrogen Starvation in Arabidopsis Root Reveals New Aspects of H2S Signaling by Protein Persulfidation

Abstract: Hydrogen sulfide (H2S)-mediated signaling pathways regulate many physiological and pathophysiological processes in mammalian and plant systems. The molecular mechanism by which hydrogen sulfide exerts its action involves the posttranslational modification of cysteine residues to form a persulfidated thiol motif. We developed a comparative and label-free quantitative proteomic analysis approach for the detection of endogenous persulfidated proteins in N-starved Arabidopsis thaliana roots by using the tag-switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 69 publications
0
53
0
Order By: Relevance
“…In recent years, many proteins have been described as sulfenylation targets in Arabidopsis in several works, revealing >2000 targets for this modification ( De Smet et al , 2019 ; Huang et al , 2019 ; Wei et al , 2020 ). In a comparison performed between the sulfenylated and the previously identified persulfidated proteins, >6000 targets ( Aroca et al , 2015 , 2017 a ; Laureano-Marín et al ., 2020 ; Jurado-Flores et al , 2021 ) revealed that 82% of the sulfenylated proteome described in Arabidopsis also undergo persulfidation ( Fig. 2A ).…”
Section: Hydrogen Sulfide Actionmentioning
confidence: 96%
See 2 more Smart Citations
“…In recent years, many proteins have been described as sulfenylation targets in Arabidopsis in several works, revealing >2000 targets for this modification ( De Smet et al , 2019 ; Huang et al , 2019 ; Wei et al , 2020 ). In a comparison performed between the sulfenylated and the previously identified persulfidated proteins, >6000 targets ( Aroca et al , 2015 , 2017 a ; Laureano-Marín et al ., 2020 ; Jurado-Flores et al , 2021 ) revealed that 82% of the sulfenylated proteome described in Arabidopsis also undergo persulfidation ( Fig. 2A ).…”
Section: Hydrogen Sulfide Actionmentioning
confidence: 96%
“…Susceptibility of several proteins to modification by sulfide has been determined ( Mustafa et al , 2009 ; Filipovic et al , 2018 ). In plants, three high-throughput proteomic analyses also revealed the presence of persulfidation in the Arabidopsis proteome, showing >3400 and 5214 proteins susceptible to persulfidation in leaf and root tissue, respectively ( Aroca et al , 2015 , 2017 a ; Jurado-Flores et al , 2021 ). Different studies on this post-translational modification of specific proteins have shown that it results in changes to the function of the proteins, altering their catalytic activity or intracellular location and inducing important physiological effects, ranging from regulation of autophagy, ABA-dependent stomatal closure, ethylene biosynthesis, and root hair growth, to resistance to oxidative stress ( Table 1 ).…”
Section: Hydrogen Sulfide Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persulfidation modulates protein functions by affecting its biochemical activity and subcellular distribution, thus providing a robust and flexible mechanism for biological regulation in response to metabolic stimuli and environmental cues [23,24]. Recently, by using a comparative and label-free quantitative proteomic analysis approach, almost 13% of the entire annotated proteome proteins were identified as being persulfidated in Arabidopsis [23,25]. These proteins are involved in a wide range of biological functions, regulating important processes such as primary metabolism, plant responses to stresses, growth and development, RNA translation, and protein degradation.…”
Section: Of 19mentioning
confidence: 99%
“…Very recently, a label-free quantitative proteomic analysis revealed that some autophagosome formation-related proteins were prone to be persulfidated, such as ATG3, ATG5, ATG7, etc. Furthermore, some proteins of initial regulatory steps for autophagy could also be persulfidated [89]. Generally, in bulk autophagy, the binding of ATG8 to phospholipid phosphatidylethanolamine (PE) is a key step in the formation of autophagosomes.…”
Section: Protein Persulfidation In Plant Autophagymentioning
confidence: 99%